[Dona Paz tragedy ; Leprosy ; Kuh Ledesma [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
Tackles the sinking of Dona Paz after 40 days ; discusses victims of leprosy in the Philippine and the basic facts about leprosy ; and the interview of singer Kuh Ledesma about her singing career.
Dona Paz tragedy (22 min.) -- Leprosy (8 min.) -- Kuh Ledesma (10 min.)
VHS.
Keywords: Ledesma, Kuh; Shipwrecks -- Philippines; Lepers -- Philippines; Leprosy -- Philippines